Safe or not safe deciding what risks to accept in our environment and food - Pechan, Paul (Springer, 2011)
Safe or Not Safe aims to present a comprehensive picture of food-related risk issues, as observed in daily life. Included are numerous real-life examples showing how scientists measure, assess, evaluate and manage potential risks, and how this helps us to decide  how to manage our food chain and ultimately the food we eat. The book is divided into four interrelated chapters. Chapter one deals with risk: Risk examples  are given from  our daily life, illustrating what we need to know about  risks and how to manage them. Chapter two addresses the risks  to biodiversity. Chapter three investigates the risks chemical contaminants pose to our health through the food chain. The final chapter reviews the last three decades of creating genetically engineered food, focusing not only on the science behind the technology, but also on issues, such as consumer choice and rights, politics, product usefulness, and the availability of alternatives. Aimed especially at food science professionals and educators, undergraduate and graduate students, health professionals, and an interested general public will also benefit greatly from this resource.